2009
DOI: 10.2353/jmoldx.2009.090003
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacogenetics of Solid Tumors: Directed Therapy in Breast, Lung, and Colorectal Cancer

Abstract: Genetic variability in drug-metabolizing enzymes and signaling pathways affects chemotherapy-related toxicity and treatment outcome in cancer. In breast and colorectal cancer , polymorphisms in metabolic enzymes involved in tamoxifen and irinotecan therapies has led the U.S. Food and Drug Administration to address genetic factors relevant to patient consideration of treatment with these compounds. Tamoxifen therapeutic failure in breast cancer has been associated with reduced CYP2D6 activity due to inefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 80 publications
(80 reference statements)
0
6
0
Order By: Relevance
“…In cancer patients, the hereditary polymorphism of enzymes are accountable for signaling paths and biotransformation of drug due to which adverse effects happen upon administration of chemotherapeutic agents [47]. This is also recognized that the chemotherapeutic agents are not selective for just cancer cells and they influence cell lines conveying higher growth and imitation rates.…”
Section: Discussionmentioning
confidence: 99%
“…In cancer patients, the hereditary polymorphism of enzymes are accountable for signaling paths and biotransformation of drug due to which adverse effects happen upon administration of chemotherapeutic agents [47]. This is also recognized that the chemotherapeutic agents are not selective for just cancer cells and they influence cell lines conveying higher growth and imitation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Uridine diphosphate glucuronosyltransferase 1A1 (UGT1A1) is involved in metabolizing Irinotecan's more potent metabolite SN-38 to inactive SN-38-glucuronide. For patients with the reduced activity UGT1A alleles, treatment with Irinotecan may result in increased toxicity [117] . Hence, prospective genotyping of the UGT1A locus would facilitate optimizing the chemotherapy for individual patients.…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
“…However, a recent study by Uzilov et al has shown that using integrative genomic approaches in the clinical setting for colorectal, breast, and medullary thyroid carcinomas has led to significantly enhanced personalized therapeutic strategies for clinicians [114] . Thus, we believe that integrating genomic findings into clinics and hospitals will provide more effective patient stratification and guide therapeutic options Although targeted therapy is a hallmark in the treatment of blood cancers, such as leukemia, there has been a wealth of successful pharmacogenomic discoveries in solid tumors as well [115][116][117] . These include Tamoxifen in treating ER+ breast cancer and EGFR-directed therapies for lung cancer patients [117] .…”
Section: Current Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In CRC and lung cancers, somatic mutations in the EGFR and downstream signaling molecules have been associated with the therapeutic outcome of EGFR-directed therapies. Current advances in single gene-UGT1A1, CYP2D6, EGFR, and K-ras-or multigene analysis contribute to optimizing breast, colorectal, and lung cancer therapy, highlighting how pharmacogenetics has helped in personalized decision-making for patient management (Snozek et al 2009 ).…”
Section: Pharmacogenetics Of Cancer Chemotherapymentioning
confidence: 99%